2014
DOI: 10.2174/0929866521666140926121716
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effect of Macromolecular Crowding on Aggregation Behaviour of a Model Amyloidogenic Peptide

Abstract: Accumulation of ordered protein aggregates (or amyloids) represents a hallmark of many diseases (e.g., Alzheimer's disease, type II diabetes, Parkinson's diseases etc.), results from intermolecular association of partially unfolded proteins/ peptides. Such associations usually take place in highly crowded conditions. The aggregates, which are formed under in vitro and in vivo conditions exhibit substantial variations in their structure and function. Such heterogeneities in amyloids might arise due to macromole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The idea that macromolecular crowding can modulate the aggregate heterogeneities was also supported by the analysis of the effects of macromolecular crowding on amyloid formation of a model amyloidogenic peptide (RATQIPSYKKLIMY) derived from the C -terminal region (amino acids 248–286) of PAP [ 306 ]. This analysis revealed that the addition of macromolecular crowding agents affected the morphology of the amyloid fibrils formed by this peptide leading to the formation of shorter amyloid aggregates, thereby supporting the hypothesis that the heterogeneous classes of aggregates can be favored by macromolecular crowding [ 306 ].…”
Section: What Can Macromolecular Crowding Do To a Proteinmentioning
confidence: 99%
“…The idea that macromolecular crowding can modulate the aggregate heterogeneities was also supported by the analysis of the effects of macromolecular crowding on amyloid formation of a model amyloidogenic peptide (RATQIPSYKKLIMY) derived from the C -terminal region (amino acids 248–286) of PAP [ 306 ]. This analysis revealed that the addition of macromolecular crowding agents affected the morphology of the amyloid fibrils formed by this peptide leading to the formation of shorter amyloid aggregates, thereby supporting the hypothesis that the heterogeneous classes of aggregates can be favored by macromolecular crowding [ 306 ].…”
Section: What Can Macromolecular Crowding Do To a Proteinmentioning
confidence: 99%
“…As the rigid DNA filament reaches a certain length, it has the capacity to ''reset'' the confining ''Tube''. The overall scaling relationship can be described by eqn (3) or (4). It has been reported that a protein or polymer chain is to scale with the confining size, with an exponent being 5/3 and 15/4 in the weak confinement regime or strong confinement regime, respectively.…”
Section: Notes and Referencesmentioning
confidence: 99%
“…It is reported that the C‐terminal part of PAP 248‐286 is crucial for the amyloid formation, as deletion of the 283 LIMY 286 region from full‐length peptide abrogated the amyloid formation by PAP 248‐286. Moreover, in our previous study, we also have reported fibril formation ability of the C‐terminal fragment (PAP 273‐286 ) . It is assumed that the formation of beta‐sheet structures during amyloidogenic aggregation commonly precedes the formation of transient helical conformation .…”
Section: Resultsmentioning
confidence: 91%
“…In human semen, macromolecular crowding and the presence of lipids are two most critical components that are known to influence the aggregation of amyloidogenic peptides. Our previous study suggests that in the presence of macromolecular crowding agents, PAP 248‐286 forms shorter fibrils with few nonfibrillar aggregates . Conceptually, smaller aggregates including protofibrillar and oligomeric conformers are critical in defining their functional characteristics.…”
Section: Introductionmentioning
confidence: 98%